2018
DOI: 10.5455/njppp.2018.8.0100812012018
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain analysis of heart rate variability in young obese adults with parental history of hypertension during isotonic exercise: A comparative study

Abstract: Background: Heart rate variability (HRV) is the beat-to-beat variation in time of consecutive heartbeats. It is one of the indicators of autonomic nervous system (ANS) function. The ANS control of the cardiovascular system in obesity and hypertension remains controversial. Aims and Objectives: The objectives of the study were to analyze the effects of isotonic exercise on frequency domain indicators of HRV in young obese adults with parental history of hypertension and compare the same with that of normal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The high body fat with low sympathetic activity in young healthy adult signi ies that body fat percentage also in luence cardiac sympathovagal balance in healthy adults (Krishna and Navekar, 2013;Wu et al, 2008). Studies have shown that susceptible individuals who have obesity and parental hypertension show a strong sympathetic overactivity due to decrease parasympathetic control, which may cause cardiovascular, risks in future (Sreenivas et al, 2018). Study has also revealed that in overweight subjects there was no difference in LF, but they had reduced HF, increased LF/HF compared to normal weight subjects (Krishna and Navekar, 2013) Imbalance of the autonomic nervous system for a prolonged duration of time is anExtensive and in luential risk factor for adverse cardiovascular events, including mortality (Curtis and Keefe, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high body fat with low sympathetic activity in young healthy adult signi ies that body fat percentage also in luence cardiac sympathovagal balance in healthy adults (Krishna and Navekar, 2013;Wu et al, 2008). Studies have shown that susceptible individuals who have obesity and parental hypertension show a strong sympathetic overactivity due to decrease parasympathetic control, which may cause cardiovascular, risks in future (Sreenivas et al, 2018). Study has also revealed that in overweight subjects there was no difference in LF, but they had reduced HF, increased LF/HF compared to normal weight subjects (Krishna and Navekar, 2013) Imbalance of the autonomic nervous system for a prolonged duration of time is anExtensive and in luential risk factor for adverse cardiovascular events, including mortality (Curtis and Keefe, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…LF and HF can be also measured in normalized units (nu) to emphasize the controlled and balanced behaviour of the two branches of the autonomic nervous system (Brar et al, 2015). Studies were reported that BMI and HRV has a very strong correlation in high blood pressure and obese young individuals (Sreenivas et al, 2018). The present study was carried out to assess the relationship between body mass index and changes of the autonomic system in heart rate variability among young female medical students.…”
Section: Introductionmentioning
confidence: 95%